The prospective study of change of perception of postgraduate students on objective structured clinical examination in burns and plastic surgery - Mohd Altaf Mir; Debarati Chattopadhyay; Madhubari Vathulya; Vishal Mago; Rajesh Kumar Maurya; Akshay Kapoor; Neeraj Rao (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: In this study, we attempted to assess the change of perception of postgraduate students on objective structured clinical examination (OSCE) in burns and plastic surgery after first five OSCE. METHODS: A prevalidated feedback questionnaire was used to assess and score the perception of postgraduate students on OSCE in burns and plastic surgery. The opinion of postgraduate students on the feedback questionnaire after first and fifth assessment tests based on OSCE was analyzed. The results were compiled on a data sheet and analyzed using Microsoft Excel and plotted as graphical interpretation. The statistical analysis was done using MedCalc software. RESULTS: The results of the study showed that there is a positive change in perception of students in favor of monthly assessment based on OSCE in burns and plastic surgery after fifth assessment. The mean students' favorable perception score after the first assessment with was 30.2 ± 2.828 (mean ± standard deviation [SD]) and after fifth assessment, 43 ± 2.828 (mean SD) with Student's test t = 10.119 and P < 0.0001 which is highly significant statistically in favor of OSCE after fifth assessment. CONCLUSIONS: We observed in our study that the monthly assessment based on OSCE is well accepted by the students of our subspecialty after few assessments; however, further studies are required to augment the evidence.